KAJIAN FILSAFAT HUKUM TENTANG DEMOKRASI DI INDONESIA - Riski Febria Nurita (Jurnal Cakrawala Hukum, 2017)
Democracy is a long process passing through habit, learning, and comprehension. For this goal, social support and democratic surroundings are needed. Democracy success is shown through how far the democracy as the principal and life reference inter citizens is done and obeyed. Democracy is a political and ethic set which develop dynamically. In reality, democracy is a group of people who are able to manage the country. It means the people who hold and manage the country must be those who have statesmen soul. It means they really revere the democracy highly used as the principle in pertaining to form government in Indonesia. Democracy which is really for people is not like the democracy applied in Indonesia today where the state holders and the organizers are busy with their own business. They take a decision by relying on their own interest without any sensitiveness to see the condition of people today. Mobocracy has really happened in Indonesia by appearing the corruptors, the law bribers, the position bribers, so democracy in Indonesia is really dead democracy if there is government that really holds firmly the democracy and is not sensitive to what the people want. Then it is true what Aristoteles says that if the people are stillmobos, do not insist the democracy in that country.